ANALISIS FATWA MUI DAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TENTANG STATUS ANAK DI LUAR PERKAWINAN (Jurnal De Jure Muhammadiyah Cirebon, 2020)
Islamic law which has been generally understood, the validity of a marriage will determine the legal position of the children born. However, the Constitutional Court in Decision Number 46 / PUU-VIII / 2010 places more emphasis on biological importance only. The position of the child resulting from adultery is now the same as a child born from a legal marital relationship. Therefore, the ruling of the Constitutional Court is considered to legalize extramarital relations without worrying about the future of children. This perception is formed because even though not bound by marriage, children resulting from adultery relations still have the right to support, marriage, marriage guardianship, and inheritance.Keywords: Child Status, Marriage, Constitutional Court, MUI Fatwa